2001
DOI: 10.1097/00005537-200108000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Papilloma: A Review of 53 Cases

Abstract: Aggressive initial management remains the therapeutic aim in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 33 publications
8
30
1
3
Order By: Relevance
“…The incidence of malignant alteration in the present study was 6.9% (5/72). This result also correlates with findings of some recent series, ranging from 6% (3/53) [68], 8.8% (3/ 34) [69], to 9% (8/89) [10]. So as to avoid a possible influence of different methodologies of HPV detection, we have summarized 16 studies in which PCR was used in order to try to obtain reliable information of HPV infection in IPsSCC [22, 23, 28-31, 33, 36, 38, 40, 42, 44, 70-72].…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of malignant alteration in the present study was 6.9% (5/72). This result also correlates with findings of some recent series, ranging from 6% (3/53) [68], 8.8% (3/ 34) [69], to 9% (8/89) [10]. So as to avoid a possible influence of different methodologies of HPV detection, we have summarized 16 studies in which PCR was used in order to try to obtain reliable information of HPV infection in IPsSCC [22, 23, 28-31, 33, 36, 38, 40, 42, 44, 70-72].…”
Section: Discussionsupporting
confidence: 93%
“…3 Several associations between inverted papilloma and SCC have been reported, including (1) synchronous SCC within an inverted papilloma, (2) focal areas of carcinoma in situ within an inverted papilloma, (3) areas of inverted papilloma inside an SCC, (4) metachronous SCC not associated with the original site of the inverted papilloma, and (5) metachronous SCC at the original site of the inverted papilloma, otherwise known as malignant transformation. 20,23 Benninger et al 24 described SCC as being a synchronous lesion in most cases. It is therefore extremely important to evaluate the entire specimen for possible malignant associations.…”
Section: Discussionmentioning
confidence: 99%
“…Facial pain, hyposmia, anosmia, and epiphora were rarely encountered. The most frequent symptom of nasal obstruction, was observed in 80 to 98% of the patients (12,13). In patients with simultaneous association of IP and malignancy, epistaxis was the most common symptom (12).…”
Section: Current Advances In the Basic Research And Clinical Managemementioning
confidence: 99%
“…However, some authors also observed patients with a history of symptoms of up to 5 years with no obvious progression of tumor growth (13,14).…”
Section: Current Advances In the Basic Research And Clinical Managemementioning
confidence: 99%